EVALUASI PEMBELAJARAN SEJARAH BERBASIS UNIT KEGIATAN BELAJAR MANDIRI (UKBM) DIMASA PANDEMI COVID-19 - Hasan, Zainul (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2022)
In 2017, schools that have implemented the SKS were given a task by the government to implement learning based on the Independent Learning Activity Unit (UKBM). The policy regarding the implementation of UKBM is on a national scale and one of the regions that implements this system is Malang City, because quite a number of schools have implemented the Semester Credit System (SKS). One of the schools that implements the Semester Credit System is SMAN 1 Malang. Learning conditions have then changed since the COVID-19 pandemic hit in March 2020. Learning activities that were originally carried out directly have changed online so it needs to be evaluated considering a program that is relatively new and new conditions. Evaluation of the learning process of Indonesian history and the history of specialization in this study uses the Context, Input, Process and Product (CIPP) model. Research activities are carried out with a qualitative approach which includes several data collection methods such as observation, interviews and documentation. The results of the Process evaluation showed that the Indonesian History subject was given the title "Not Good" with a percentage of 45.5 percent. The Specialization History subject group received a "Good" predicate with a percentage of 62.9 percent. This difference lies in the learning process for the History of Specialization, which has conducted face-to-face online learning before the PAS implementation which contains an explanation of the preparation of the assessment. KEYWORDS Evaluation, UKBM, CIPP. Pada tahun 2017, sekolah yang sudah menerapkan SKS diberikan tugas oleh pemerintah untuk menerapkan pembelajaran berbasis Unit Kegiatan Belajar Mandiri (UKBM). Kebijakan mengenai penerapan UKBM ini berskala Nasional dan salah satu daerah yang menerapkan sistem ini adalah Kota Malang, karena cukup banyak sekolah yang sudah menerapkan Sistem Kredit Semester (SKS). Salah satu sekolah yang menerapkan Sistem Kredit Semester adalah SMAN 1 Malang. Kondisi pembelajaran kemudian berubah sejak pandemi covid-19 melanda bulan Maret 2020. Aktivitas pembelajaran yang semula dilakukan secara langsung berubah online sehingga perlu untuk di evaluasi mengingat sebuah program yang tergolong baru dan kondisi yang baru. Evaluasi pada proses pembelajaran sejarah indonesia dan sejarah peminatan pada penelitian ini menggunakan model Context, Input, Process and Product (CIPP). Kegiatan penelitian dilakukan dengan pendekatan kualitatif yang didalamnya mencakup beberapa metode pengumpulan data seperti observasi, wawancara dan dokumentasi. Hasil evaluasi Process menunjukkan bahwa mata pelajaran Sejarah Indonesia mendapat predikat “Kurang Baik” dengan persentase 45.5 persen. kelompok mata pelajaran Sejarah Peminatan mendapatkan predikat “Baik” dengan persentase 62.9 persen. Perbedaan ini terletak pada proses pembelajaran Sejarah Peminatan yang pernah melakukan pembelajaran tatap muka secara online menjelang pelaksanaan PAS yang berisikan penjelasan persiapan penilaian.